Depth-dependent density change within the continental upper mantle - TENZER, Robert; BAGHERBANDI, Mohammad; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2012)
The empirical model of the depth-dependent density change within the uppercontinental mantle is derived in this study. The density of the upper(most) mantle underlyingthe continental crust is obtained from the estimated values of the crust–mantle(Moho) density contrast. Since the continental crustal thickness varies significantly, theseupper mantle density values to a large extent reflect the density changes with depth. Theestimation of the Moho density contrast is done through solving Moritz’s generalizationof the Vening-Meinesz inverse problem of isostasy. The solution combines gravity andseismic data in the least-squares estimation model. The estimated upper mantle density(beneath the continental crust) varies between 2770 and 3649 kg/m3. The upper mantledensity increases almost proportionally with depth at a rate of 13±2 kg/m3 per 1 km atthe investigated depth interval from 6 to 58 km.